The Synthesis of Waltherione F and Its Analogues with Modifications at the 2‐ and 3‐Positions as Potential Antitrypanosomal Agents. Issue 5 (20th December 2018) - Zdorichenko, Victor; Paumier, Romain; Whitmarsh‐Everiss, Thomas; Roe, Mark; Cox, Brian
Abstract: Chagas disease also know as American Trypanosomiasis (AT) is a tropical parasitic disease endemic in South America, is caused by Trypanosoma cruzi, which is transmitted by the blood‐sucking insect vectors called triatomine bugs. Quinoline alkaloids from the root extract of Waltheria indica are known to possess antitrypanosomal activity. Waltherione F, one of those alkaloids, was synthesised in 5 steps in 11 % overall yield. We report here the first X‐ray crystallographic confirmation of the structure of Waltherione F3 . A key step in the sequence utilised the Conrad–Limpach synthesis for the formation of the quinolin‐4(1 H )‐one ring system. Our synthetic strategy was designed to enable the modification of the 2‐ and 3‐positions of the scaffold, allowing the generation of a diverse library of analogues to support our on‐going medicinal chemistry program that is looking for new agents to tackle this devastating disease. Abstract : Waltherione F and analogues : Potential antitrypanosomal agents synthesized utilising the Conrad–Limpach synthesis for the formation of the quinolin‐4(1 H )‐one ring system a key step in the sequence. A diverse library of analogues was prepared with modifications to the 2‐ and 3‐positions of the scaffold to support our on‐going medicinal chemistry program that is looking for new agents to tackle this devastating disease.